HIV-Infected Individuals Do Not Present Significant Differences regarding Periodontal Status: A Systematic Review and Meta-Analysis - Lucas Ribeiro Teixeira; Diana Estefania Ramos Peña; Leticia Rodrigues de Castro; Márcia dos Santos; Maria da Conceição Pereira Saraiva; Fernando Chahud; Bruno Pozzetto; Alan Grupioni Lourenço; Ana Carolina Fragoso Motta (Hindawi Limited, 2024)
Objective. To evaluate, through a systematic literature review, whether periodontal status in HIV-infected individuals is different from those non-HIV-infected. Materials and Methods. A systematic search for published observational studies within six electronic databases and grey literature was conducted, PROSPERO database number CRD42020160062. Results from studies reporting clinical periodontal parameters: probing pocket depth, bleeding on probing, clinical attachment level, plaque index, and gingival index, in HIV- and non-HIV-infected individuals were reviewed. The quality of the assessment was evaluated according to the Joanna Briggs Institute Appraise Checklist. Results. Twenty-three observational studies met the eligibility criteria and were included for analysis. The qualitative analysis indicated similarities in periodontal parameters within both groups, with no significant mean difference (MD) within both groups regarding clinical periodontal parameters; severe heterogeneity was also detected. Conclusions. No significant differences were found in the periodontal profile of HIV-infected and non-HIV-infected individuals. However, the high heterogeneity among the studies calls for caution in interpreting these findings. Further investigations using standardized methods for periodontal evaluation are needed to clarify the association between HIV infection and periodontal conditions.